SHAPING MEMORIES, SHARPENING MINDS: UTILIZING THE MNEMONIC METHOD TO ENHANCE STUDENTS' UNDERSTANDING OF ILM SHARF - Kadir, Suleman D.; Yasin, Zohra; Abdullah, Abdullah; Jundi, Muhammad; Hasibuan, Renni (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research addresses the prevalent use of traditional rote memorization strategies in Islamic schools, which result in lengthy learning processes and student boredom. In the study of Ilm Sharf, distinguishing harakat in triliteral verbs (tsulatsi mujarrad) is crucial. To address this, the researcher proposes the Mnemonic method as a solution for quicker material retrieval. The research question is: Does the Mnemonic method impact the learning outcomes of Ilm Sharf at Al-Falah Islamic Boarding School in West Limboto? This experimental quantitative study involves two groups: an experimental group and a control group. Instruments used include pre-tests, post-tests, and questionnaires. The findings indicate that the Mnemonic method facilitates the learning process and understanding of Ilm Sharf basics. It helps students easily distinguish harakat in words within the wazn tsulatsi mujarrad, such as imperative and prohibitive verbs. Moreover, the Mnemonic method significantly improves learning outcomes. The t-test results show t-count = 4.5, which is greater than the t-table values at 1% (2.44) and 5% (1.69) significance levels. Thus, the research hypothesis is accepted, concluding that the Mnemonic method has a significant effect on learning Ilm Sharf